Pengaruh Perputaran Piutang Dan Perputaran Modal Kerja Terhadap Likuiditas Pada PT.Chandra Asri Petrochemichal,Tbk.: perputaran piutang ; perputaran modal kerja ; likuiditas - Firli Agusetiawan Shavab; Fuadi; Yolanda Puspitasari (Sains Manajemen: Jurnal Manajemen Unsera, 2022)
The purpose of this study is to test and analyze the effect of receivables turnover and working capital turnover on liquidity partially and simultaneously in PT. Chandra Asri Petrochemical, Tbk. period 2010-2019. Where are the financial statements of PT. Chandra Asri Petrochemical, Tbk. which has been published on the Indonesia Stock Exchange (IDX) is a population as well as a sample with a research period. The sample technique used is non probability sampling. The method used is descriptive statistical analysis with a quantitative approach. The results showed that the turnover of receivables and the turnover of working capital had no effect and were significant on liquidity partially, while simultaneously the turnover of receivables and the turnover of working capital had a positive and significant effect on liquidity. The results of the coefficient of determination show that the contribution of the effect of receivables turnover and working capital turnover on liquidity is 60.9%.